Characteristics of a population of commuter cyclists in the Netherlands: perceived barriers and facilitators in the personal, social and physical environment - Hendriksen Ingrid JM; Engbers Luuk H (BMC, 2010)
Abstract Background Daily cycling to work has been shown to improve physical performance and health in men and women. It is very common in the Netherlands: the most recent data show that one quarter of commuting journeys are by bicycle. However, despite the effort going into campaigns to promote commuter cycling, about 30% of commuter journeys up to 5 kilometers are still by car. The question is how to stimulate commuter cycling more effectively. This article aims to contribute to a better understanding of the perceived barriers and facilitators of cyclists/non-cyclists and personal factors associated with commuter cycling. Methods A random sample of 799 Dutch employees (response rate 39.6%) completed an internet survey, which comprised two parts. One part of the questionnaire focused on the determinants of cycling behavior including equal numbers of personal, social factors and environmental factors. The other component focused on assessing data on physical activity (PA) behavior. Descriptive and logistic regression analyses were used to analyze factors associated with commuter cycling. Results Meeting the physical activity guideline was positively associated with commuter cycling. Television viewing and working full-time were negatively associated. Twenty-six percent of the participants met the PA guideline simply by cycling to work, with health as the main reason. The main barriers for non-cyclists (60%) were perspiration when arriving at work, weather and travelling time. Shorter travelling times compared with other transportation modes were an important facilitator. Environmental factors were positively related to more frequent and more convenient commuter cycling, but they were hardly mentioned by non-cyclists. Conclusions This study shows that a relatively large group fulfils the PA recommendations merely by cycling to work. Personal factors (i.e., perceived time and distance) are major barriers to commuter cycling and should be targeted in cycling campaigns, especially in subgroups living within cycling distance to work. Targeting environmental determinants in such campaigns seems to be less important in the Netherlands.